2020
DOI: 10.1038/s41467-020-15263-3
|View full text |Cite
|
Sign up to set email alerts
|

Additive rheology of complex granular flows

Abstract: Granular flows are omnipresent in nature and industrial processes, but their rheological properties such as apparent friction and packing fraction are still elusive when inertial, cohesive and viscous interactions occur between particles in addition to frictional and elastic forces. Here we report on extensive particle dynamics simulations of such complex flows for a model granular system composed of perfectly rigid particles. We show that, when the apparent friction and packing fraction are normalized by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 65 publications
3
54
0
1
Order By: Relevance
“…This is what we observed from 3D simulations of packings of spherical particles with capillary forces, as shown in Fig. 2 with ↵ ' 0.09 [7]. The viscous forces may be either due to the action of a saturating liquid or lubrication forces acting at the gaps between particles in wet granular materials.…”
Section: Effect Of Adhesion and Viscous Forcessupporting
confidence: 79%
See 3 more Smart Citations
“…This is what we observed from 3D simulations of packings of spherical particles with capillary forces, as shown in Fig. 2 with ↵ ' 0.09 [7]. The viscous forces may be either due to the action of a saturating liquid or lubrication forces acting at the gaps between particles in wet granular materials.…”
Section: Effect Of Adhesion and Viscous Forcessupporting
confidence: 79%
“…For example, for capillary forces, we may set 0 c = s d = f c /(⇡d 2 ), where s is the surface tension of the liquid. This di↵ers from the exact expression of c given by equation (7). For this reason, in equation (10) ⇠ should be replaced by ↵⇠.…”
Section: Effect Of Adhesion and Viscous Forcesmentioning
confidence: 98%
See 2 more Smart Citations
“…The friction coefficient and the volume fraction then become functions of the inertial number and the cohesion number: µ = µ(I, C) and φ = φ(I, C). Some numerical studies [13,14] using a simple JKR-like [15], yet non-hysteretic adhesion force model and others [16,17] using capillary adhesion force model have verified these scaling and reported that µ(I, C) and φ(I, C) increases and decreases, respectively, with increasing I and C. A new set of scaling laws involving a generalized inertial number has also been proposed [18,19].…”
Section: Introductionmentioning
confidence: 94%